2023
DOI: 10.1590/1807-3107bor-2023.vol37.0050
|View full text |Cite
|
Sign up to set email alerts
|

Acinic cell carcinoma of the oral and maxillofacial region: an international multicenter study

Abstract: The aim of this study was to describe the prevalence, clinicopathological, and prognostic features of acinic cell carcinoma (AciCC) of the oral and maxillofacial region. AciCC cases were retrospectively retrieved from 11 pathology centers of three different countries. Medical records were examined to extract demographic, clinical, pathologic, and follow-up information. A total of 75 cases were included. Females (65.33%) with a mean age of 45.51 years were mostly affected. The lesions usually presented as an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…We identified HG AciCC in 17% of cases, as in previous studies [21,26]; this prevalence was almost twice the one reported by larger case series [26,27].…”
Section: Discussionsupporting
confidence: 83%
“…We identified HG AciCC in 17% of cases, as in previous studies [21,26]; this prevalence was almost twice the one reported by larger case series [26,27].…”
Section: Discussionsupporting
confidence: 83%